Neural identification of compaction characteristics for granular soils - Kłos, Marzena; Waszczyszyn, Zenon; Sulewska, Maria (Computer Assisted Methods in Engineering and Science, 2017)
The paper is a continuation of [9], where new experimental data were analysed. The Multi-Layered Perceptron and Semi-Bayesian Neural Networks were used. The Bayesian methods were applied in Semi-Bayesian NNs to the design and learning of the networks. Advantages of the application of the Principal Component Analysis are also discussed. Two compaction characteristics, i.e. Optimum Water Content and Maximum Dry Density of granular soils were identified. Moreover, two different networks with two and single outputs, corresponding to the compaction characteristics, are analysed.